Representasi Perempuan dalam Cerpen Madju' Al -Urus dan Qissatul Fathiyyah Al-Misriyyah (Kajian Sastra Banding) - Pratma Yandrefo; Ahmad Busyrowi; Shinta Fitria Utami (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2020)
This study examines the representation of women in the short stories Madj'u Al-Urus by Khalil Ghibran and Qissatul Fathiyyah Al-Misriyyah by Nawal As-Sa'dawi. The approach used in this research is descriptive qualitative. This research is a comparative literature study with the help of feminism theory as the analytical knife. The results of this study are the self-image of women from the physical aspect depicted in the short story Fathiyyah Al-Misriyyah, a woman who has grown up is shown to experience changes in herself, namely biologically, namely being able to get pregnant, give birth and breastfeed. Meanwhile, in the short story Madj'u Al-'Urus, women are described as someone who likes to show off their body shape. In terms of the psychological aspect, women are weak figures, they experience acts of violence that make them look like crazy people. Meanwhile, Kahlil Gibran did not explain in detail the consequences of the violence he experienced. Based on the social aspect, women equally get help from other people.